Promising black locust (Robinia pseudoacacia L.) cultivars in Hungary - Rédei, K.; Keserű, Zs.; Csiha, I.; Rásó, J.; Takács, M. (International Journal of Horticultural Science, 2018)
In Hungary, black locust (Robinia pseudoacacia L.) is one of the most important exotic stand-forming tree species, growing mostly under unfavourable ecological conditions. Considering the climate change effects its importance is increasing in many other countries. As a result of a selection programme, several black locust cultivars have been improved for setting up cultivar trials. In the paper four black locust cultivars were evaluated in Central Hungary under arid hydrological and brown forest soil conditions. Significant differences (P